Bacterial leaching of uranium ore from Figueira-PR, Brazil, at laboratory and pilot scale - Júnior, O.Garcia (Wiley, 1993)
A bacterial leaching program was carried out in order to evaluate the potential of applying this process to leach uranium from the ore of Figueira-PR, Brazil. The experiments were carried out in shake flasks, column percolation (laboratory and scmipilot scale)and in heap leaching. In shake flasks and in column percolation experiments at laboratory scale, bacterial activity on Ihe ore was confirmed: approximately 60% of uranium was leached, against around 30% in sterilized controls. Colunm percolation experiments at semipilot scale and heap leaching (850 tons of ore) showed uranium extractions of approximately 50%. In both experiments, a complementary sulfuric acid attack, after the bacterial leaching phase, was neccssaw to reach this level of uranium extraction. © 1993.
Keywords: Bacterial leaching; Thiobacillus ferrooxidans